When nature needs a helping hand: Different levels of human intervention for mangrove (re-)establishment - Zimmer, Martin; Ajonina, Gordon N.; Amir, A. Aldrie; Cragg, Simon M.; Crooks, Stephen; Dahdouh-Guebas, Farid; Duke, Norman C.; Fratini, Sara; Friess, Daniel A.; Helfer, Véronique; Huxham, Mark; Kathiresan, Kandasamy; et al. (Frontiers in Forests and Global Change, 2022)
Protecting existing mangrove forests is a priority for global conservation because of the wide range of services that these coastal forests provide to humankind. Despite the recent reduction in global rates of mangrove loss, high historical loss rates mean that there are at least 800,000 ha globally that are potentially suitable for mangrove rehabilitation. Recently deposited mud banks or intertidal, previously terrestrial, land might provide additional habitat for expanding mangrove areas locally. There is a long history of mangrove rehabilitation. However, despite numerous good examples of, and growing expertise in, natural or assisted (re-)establishment activities, most mangrove planting efforts, for instance, either fail entirely or meet with only limited success. Exposed to waves and currents and subject to tidal inundation, mangroves differ from terrestrial forests, and approaches to, or tools for, terrestrial forest restoration cannot easily be transferred to mangrove forests. Successful mangrove (re-)establishment usually requires a robust understanding of the abiotic and biotic conditions of the chosen site, the ecological requirements of the mangrove species used or facilitated, the reasons for previous mangrove loss or degradation, as well as the barriers – both societal and ecological – that have prevented natural recovery to date. Because most mangrove forests are socio-ecological systems, with which local human populations are intimately engaged, (re-) establishment will normally require the support of, and engagement with, local communities and other local stakeholders. Here, we summarize where, when and why (re-)establishment of mangroves is needed and how to assess this need. We discuss a range of potential aims and goals of mangrove (re-)establishment along with potential pitfalls along the way from conceiving the initial idea to its realization. We compare different technical and conceptual approaches to mangrove (re-)establishment, their challenges and opportunities, and their design and financial requirements, as well as potential solutions. We ground our final outlook and recommendations on examples of successful efforts and the factors that rendered (re-)establishment successful in the past.